Evolution Law of Gas Discharge of Carbon Monoxide in Mining Extra-Thick Coal Seam of Datong Mining Area - Zhanyuan Ma; Feng Du (Geofluids)
In order to reveal the evolution law of gas discharge of carbon monoxide in mining an extra-thick coal seam of the Datong mining area by the numerical simulation and field monitoring test, the 8202 working face and 8309 working face in the Tongxin coal mine are chosen as the test sites. The results show that the seepage flow of carbon monoxide gas reaches 1.854×10−8 m3/s in the #1 fracture after the #3 key stratum in the far field breaks in the 8202 working face, the seepage flow of carbon monoxide gas reaches 1.307×10−7 m3/s in the #2 fracture, the seepage flow of carbon monoxide gas reaches 4.276×10−7 m3/s in the #3 fracture, the seepage flow of carbon monoxide gas reaches 4.192×10−7 m3/s in the #4 fracture, and the seepage flow of carbon monoxide gas reaches 1.623×10−7 m3/s in the #5 fracture. The initial caving of the #3 key stratum in the far field occurs and collapses to the gob, when the working face in the #3-5 coal seam advances to 180 m, and the voussoir beam forms in the #3 key stratum. Besides, a shower shape was formed by the seepage flow of carbon monoxide gas, and the maximum flow in the working face reaches 4.562×10−4 m3/s. When the 8309 working face advances from 521.2 m to 556.4 m, the air pressure at the working face gradually rises and reaches the maximum magnitude and then begins to decrease; when the working face advances to 556.4 m, the air pressure at the working face reaches the maximum magnitude of 91.35 kPa. The gas discharge disaster of carbon monoxide in mining the extra-thick coal seam of the Datong mining area is effectively controlled by the dynamic balance multipoint control technology. The research results can be treated as an important theoretical basis for the prevention and treatment for carbon monoxide discharge disaster in mining the extra-thick coal seam of the Datong mining area.